2019
DOI: 10.3390/ma12132143
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Shearing Mechanism of Finish-type FB and Extrusion-type FB for Thin Foil of JIS SUS304 by Numerical and EBSD Analyses

Abstract: A numerical analysis using FE (finite element) analysis was performed to clarify the shearing mechanism in the process of extrusion-type fine blanking (FB) for a thin foil of JIS SUS304 in this study. Extrusion-type FB, in which a negative clearance between the punch and the die has been developed and investigated experimentally to improve the quality of the sheared surface in the blanking of thin foils. The resultant sheared surface for extrusion-type FB indicated an almost completely sheared surface, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The remeshing condition was based on the possible depth of interference between the work material element and the tool boundary (specifically, this interference depth was 1 µm). Incidentally, the aforementioned FEM conditions were based on the fact that the results of the blanking experiment and the FEM analysis were in good agreement in the previous report [12]. For the punch and die, we selected cemented carbide (WC-15% Co) on the DEFORM2D software mentioned earlier.…”
Section: Fem Simulation Model and Conditionsmentioning
confidence: 91%
See 2 more Smart Citations
“…The remeshing condition was based on the possible depth of interference between the work material element and the tool boundary (specifically, this interference depth was 1 µm). Incidentally, the aforementioned FEM conditions were based on the fact that the results of the blanking experiment and the FEM analysis were in good agreement in the previous report [12]. For the punch and die, we selected cemented carbide (WC-15% Co) on the DEFORM2D software mentioned earlier.…”
Section: Fem Simulation Model and Conditionsmentioning
confidence: 91%
“…Falconnet et al reported punch wear in the blanking of a copper thin sheet [23,24]. However, the punch load due to the difference in negative clearance, including zero clearance in the FB proposed in previous reports [11,12], has not been verified or analyzed. In this study, we aim to derive the optimal clearance at which the shear cut surface can be finished with a full-sheared surface and the punch load can be minimized by experimental verification and finite element analysis at the narrow, zero, and negative clearances.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…6) Moreover, we have clarified the suppression mechanism of the fracture by an FE analysis and EBSD analysis. 7) On the other hand, focusing on materials used for medical components, austenitic stainless steels are often used as the materials from the viewpoints of both corrosion resistance and biocompatibility. In particular, JIS SUS304 and JIS SUS316L materials are used in many medical components.…”
Section: Introductionmentioning
confidence: 99%
“…Suzuki et al [ 39 ] elucidated the shearing mechanism of finish-type FB and extrusion-type FB for a thin foil of JIS SUS304 by numerical and EBSD analyses. In this research, a numerical analysis using finite element (FE) analysis was performed to clarify the shearing mechanism in the process of extrusion-type fine blanking (FB) for a thin foil of JIS SUS304.…”
mentioning
confidence: 99%